Faktor-faktor yang Berhubungan dengan Kejadian Preeklampsi Pada Ibu Hamil Trimester III pada Praktik Mandiri Bidan X di Bangkalan - Zainiyah, Zakkiyatus; Harahap, Dewi Anggriani (LPPM Hang Tuah Pekanbaru, 2023)
Preeclampsia is hypertension at 20 weeks of gestation or after delivery with blood pressure ≥ 140/90 mmHg accompanied by protein in the urine and edema. Preeclampsia can occur during pregnancy, childbirth, and puerperium. During pregnancy, preeclampsia occurs at the age of 20 weeks and above. The study aimed to analyze the factors associated with the occurrence of preeclampsia. The research method was analytic with a cross-sectional approach. The independent variables are age, education, occupation, anxiety, and adherence to antenatal care, the dependent variable is preeclampsia. The population is 42 children with a sample of 38 respondents. Simple random sampling technique, statistical test using Spearman Rank. The data analysis used was univariate with percentage, and bivariate with Spearman Rank. The statistical test results obtained P-value (0.010) < α (0.05) anxiety, P-value (0.001) < α (0.05) adherence to antenatal care, age P-value (0.000), occupation P-value (0.003) and P-value (0.04) with the incidence of preeclampsia. Efforts to reduce the incidence of preeclampsia are by encouraging pregnant women to carry out regular and active Ante Natal Care examinations to attend classes for pregnant women. Early detection of preeclampsia is still being carried out for all pregnant women to prevent preeclampsia.